Deficiência visual: desafios da acessibilidade ao mundo laboral - Rocha, Roselandia Maria Serra Verde Coelho (Universidade do Vale do Rio dos Sinos, 2018)
This thesis argues that the Social Theory of Disability – focused on the protests formed by people with disabilities in the international (1970-1980) and national movements (1975-1990) - has added significant advances, but it still has little relevance to the professional development of the person with visual impairment. The local movement is insufficient to influence public policies and assistance institutions for the training and professionalization of these social actors, who face great difficulties in this field. This conclusion was based on the observation made in Bahia Association of Blind people, which has been mobilized since 1985 for the formation, qualification and referral of blind people to the world of work. The research corpus is formed by a set of data collected through individual and semi-directive interviews with a narrative focus as well as observations of the daily routine at the research locus. The transformations and permanence were analyzed using Laurence Bardin's Content Analysis technique. The issue of subjectivities linked to the processes of professional formation, its identity and professional ethos, is also discussed. The delineating contours of paradigmatic overcoming, between advances and setbacks, individually and collectively, of the subjects in the epigraph are highlighted. The thesis is based on the main theoretical articulators: Alberto Melucci and the idea of social movements as collective actions; the identity issue and the professional ethos according to the contemporary cultural studies, with Stuart Hall, Kathryn Woodward, and Tadeu Tomaz da Silva; the conceptual and argumentative application on the processes of identities by José Ivo Follmann, who states that "the human being is a being of projects; Hannah Arendt and the category of analysis through the three pillars: labor, work and action. The results of the research indicate the great difficulties encountered by the individuals who become professionals and try to enter the world of work. Another subset of this universe is composed of individuals who feel unmotivated to enter the process of qualification and / or professionalization, adopting informality as an alternative way of living and working. The Quota Law has not avoided that the demands of the world of work become an obstacle for visually impaired people. However, this set of people presents emancipatory possibilities, through the visibility of their identity processes, if they are offered adequate public policies and a dive in the professional field. Its collectivity can offer singularizing modes of subjectivation, allowing the concrete practice to be able to make the transition from the arendtian stage of animal laborans” to “Homo faber”.
Keywords: Deficiência visual; Profissiografia; Processos de identidades; Labor; Visual impairment; Social movements; Identity processes; ACCNPQ::Ciências Humanas::Sociologia